The contribution of psychological capital in improving work-family balance in female entrepreneurs - Saputri, A. Tiara Alfiani; Muis, Ismarli; Anwar, Hilwa (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
The flexibility of entrepreneurship allows individuals to set their working hours. However, juggling family responsibilities with work demands can increase stress for female entrepreneurs. This study investigates the impact of psychological capital, including self-efficacy, hope, resilience, and optimism, on the work-family balance of female entrepreneurs. The research involved 302 female entrepreneurs who completed the Work-Family Balance Scale and the Psychological Capital Questionnaire (PCQ) through an online survey. The research suggests that psychological capital positively influences work-family balance and emphasizes the significant role of self-efficacy and resilience as the primary predictor of work-family balance. Moreover, the duration of business operation, educational attainment, and the size of the workforce were found to have a notable impact on work-family balance. Interestingly, the number of children was determined to have no effect.